Pengurusan Piutang Negara Pada Kementerian/Lembaga Dalam Perspektif Hukum Perdata (Studi Pada KPKNL Medan) - Novida Helen Bariang; Dani Sintara; Halimatul Maryani; Adawiyah Nasution (Universitas Medan Area, 2022)
This study aims to find out the problems that often occur for the Committee for State Receivable Affairs (PUPN) in carrying out their duties assisted by the Directorate General of State Assets (DJKN). DJKN carries out collection of receivables based on Minister of Finance Regulation (PMK) Number 240 of 2016 concerning the management of state receivables. DJKN is entrusted with the authority by PUPN to collect uncollectible state receivables. Collection of state receivables by DJKN in order to collect state rights and return them to the state. This study uses normative legal research that is descriptive analytical based on a case approach which is then analyzed qualitatively. The results of the study indicate that in essence there is a need for transparency of procedures from DJKN in collecting state receivables. DJKN delegates this authority to the State Assets and Auction Service Office (KPKNL) as the executor of the management of state receivables in accordance with PMK Number 240 of 2016, in the management of receivables, it is necessary to analyze the aspects of civil law